Synthesis and characterization of an Fe-MOF@Fe3O4 nanocatalyst and its application as an organic nanocatalyst for one-pot synthesis of dihydropyrano[2,3-c]chromenes - Sheikhhosseini, Enayatollah; Yahyazadehfar, Mahdieh (Frontiers in Chemistry, 2023)
In this study, the recyclable heterogeneous cluster bud Fe-MOF@Fe3O4 nanoflower composite (CB Fe-MOF@Fe3O4 NFC) was successfully synthesized using Fe(NO3)3.9H2O, 8-hydroxyquinoline sulfate monohydrate and Fe3O4 nanoparticles by microwave irradiation. The characterization of as-prepared CB Fe-MOF@Fe3O4 NFC was confirmed with various characterization techniques such as X-ray diffraction (XRD), field emission scanning electron microscope (FE-SEM), energy dispersive X-ray spectroscopy (EDX), vibrational sampling magnetometer (VSM) and Fourier transform spectroscopy infrared (FTIR). Moreover, the CB Fe-MOF@Fe3O4 NFC samples proved to have excellent catalytic activity. The catalytic activity of CB Fe-MOF@Fe3O4 NFC nanoparticles was explored in the synthesis of dihydropyrano[3, 2-c]chromene derivatives via a three-component reaction of 4-hydroxycoumarin, malononitrile, and a wide range of aromatic aldehyde compounds. Optimized reaction conditions led to several advantages, including the use of water as a green solvent, environmental compatibility, simple work-up, the use of a reusable catalyst, little catalyst loading, faster reaction and high yields.